2010
DOI: 10.1016/s1976-1317(11)60005-4
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion and Related Factors Among Korean Goose Mothers

Abstract: The findings of this study contributed to the body of knowledge of health promotion among international migrant populations by identifying the differential effects of social support, acculturation attitudes, and perceived family health for six areas of health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
14
1
2
Order By: Relevance
“…The total HPLP score reported by our study participants was lower than the score reported by immigrant women in the United Sates (Cha, 2010) and higher than those of workers in the food industry in Turkey (Beşer et al, 2007) and of skilled and unskilled workers in Taiwan (Huang et al, 2010). The most frequently practiced health behavior was spiritual growth, followed by interpersonal relationships, nutrition, health responsibility, and stress management.…”
Section: Discussioncontrasting
confidence: 62%
“…The total HPLP score reported by our study participants was lower than the score reported by immigrant women in the United Sates (Cha, 2010) and higher than those of workers in the food industry in Turkey (Beşer et al, 2007) and of skilled and unskilled workers in Taiwan (Huang et al, 2010). The most frequently practiced health behavior was spiritual growth, followed by interpersonal relationships, nutrition, health responsibility, and stress management.…”
Section: Discussioncontrasting
confidence: 62%
“…Outro estudo analisou as "mães gansos" coreanas (termo utilizado para as mães que migram para outros países por um período de tempo prolongado para promover educação aos seus filhos, porém seguem casadas com seus esposos que ainda residem na Coreia) na qual foram investigado seus comportamentos de promoção da saúde na área da América do Norte. Utilizou-se para coleta um questionário demográfico criado pelo autor e a Health Promotion Lifestyle Profile (HPLP) que mede as frequências dos comportamentos de promoção da saúde em seis áreas: auto realização, responsabilidade para saúde, atividade física, nutrição, relação interpessoal, e gestão do stress (12) . O ensaio clínico randomizado, realizado com usuários de metanfetamina em recuperação e membros da família, utilizou para sua coleta de dados o Modelo de Promoção da Saúde de Pender (PHPM) e o Modelo de Empoderamento Centrado na Família (FCEM) para avaliar uma intervenção educativa (13) .…”
Section: Metodologias Para Promoção Da Saúde Familial Nos Diferentes unclassified
“…Os estudos também buscam resgatar as dimensões da promoção da saúde vividas no dia a dia da família como a cultura, os fatores sociais, as atividades que envolvem mudança de comportamento como atividade física e nutrição, além das relações interpessoais, apontando quão complexo e variado são os cuidados para a promoção da saúde (12) . Deste modo, a Promoção da Saúde da Família envolve ações de saúde para e com a família, a partir das experiências do seu dia a dia e da construção e manutenção de rotinas.…”
Section: Metodologias Para Promoção Da Saúde Familial Nos Diferentes unclassified
“…"Wild-geese families 1 ," a typical type of transnational family in Korea, refers to families in which children and wives travel to English-speaking countries to pursue education while husbands remain at home to provide financial support (Cha 2010;Cho 2004Cho , 2005Finch and Kim 2012;Kim 2010;Lee and Koo 2006). Transnational families including wild-geese families and other types have emerged in pursuit of a better education, but they are not unique only to East Asian countries.…”
Section: Introductionmentioning
confidence: 99%